Cumulative Application of Creatinine and Urine Output Staging Optimizes the Kidney Disease: Improving Global Outcomes Definition and Identifies Increased Mortality Risk in Hospitalized Patients With Acute Kidney Injury - Sutherland, Scott M; Kaddourah, Ahmad; Gillespie, Scott E; Soranno, Danielle E; Woroniecki, Robert P; Basu, Rajit K; Zappitelli, Michael (Critical care medicine, 2021)
Acute kidney injury is diagnosed according to creatinine and urine output criteria. Traditionally, both are applied, and a severity stage (1-3) is conferred based upon the more severe of the two; information from the other criteria is discarded. Physiologically, however, rising creatinine and oliguria represent two distinct types of renal dysfunction. We hypothesized that using the information from both criteria would more accurately characterize acute kidney injury severity and outcomes. Prospective cohort study. Multicenter, international collaborative of ICUs. Three thousand four hundred twenty-nine children and young adults admitted consecutively to ICUs as part of the Assessment of the Worldwide Acute Kidney Injury, Renal Angina and Epidemiology Study. The Kidney Disease: Improving Global Outcomes creatinine and urine output acute kidney injury criteria were applied sequentially, and the two stages were summed, generating an Acute Kidney Injury (AKI) Score ranging from 1 to 6. The primary outcome was 28-day mortality; secondary outcomes were time until ICU discharge and nonrecovery from acute kidney injury. Models considered associations with AKI Score, assessing the relationship unadjusted and adjusted for covariates. Twenty-eight-day mortality and nonrecovery from acute kidney injury were modeled using logistic regression. For 28-day ICU discharge, competing risks analysis was performed. Although AKI Scores 1-3 had similar mortality to no Acute Kidney Injury, AKI Scores 4-6 were associated with increased mortality. Relative to No Acute Kidney Injury, AKI Scores 1-6 were less likely to be discharged from the ICU within 28 days. Relative to AKI Score 1, AKI Scores 2-6 were associated with higher risk of nonrecovery. Within the traditional Kidney Disease: Improving Global Outcomes Stage 3 acute kidney injury cohort, when compared with AKI Score 3, AKI Scores 4-6 had increased mortality, AKI Scores 5-6 had prolonged time to ICU discharge, and AKI Score 6 experienced higher nonrecovery rates. Cumulative application of the creatinine and urine output criteria characterizes renal excretory and fluid homeostatic dysfunction simultaneously. This Acute Kidney Injury score more comprehensively describes the outcome implications of severe acute kidney injury than traditional staging methods.